A rigorous method to enrich for exosomes from brain tissue. Issue 1 (1st December 2017) - Vella, Laura J.; Scicluna, Benjamin J.; Cheng, Lesley; Bawden, Emma G.; Masters, Colin L.; Ang, Ching‐Seng; Willamson, Nicholas; McLean, Catriona; Barnham, Kevin J.; Hill, Andrew F.
ABSTRACT: Extracellular vesicles, including exosomes, are released by all cells, including those of the nervous system. Capable of delivering lipid, protein and nucleic acids to both nearby and distal cells, exosomes have been hypothesized to play a role in progression of many diseases of the nervous system. To date, most analyses on the role of these vesicles in the healthy and diseased state have relied on studying vesicles from in vitro sources, such as conditioned cell culture media, or body fluids. Here we have taken a critical approach to the enrichment and characterization of exosomes from human frontal cortex. This method maintains the integrity of the vesicles and their cargo, and comprehensive proteomic and genomic characterization confirms the legitimacy of the resulting extracellular vesicles as endosome‐derived exosomes. This method will enable neuroscientists to acquire more detailed information about exosomes in the brain and explore the role(s) this form of intercellular communication and unique source of lipid, protein and RNA has in healthy brain function and pathogenic conditions. Furthermore, this method may have important utility in the isolation of exosomes from other tissues.